Neurodevelopment and timely early stimulation in children of indigenous migrant and non-migrant mothers in Chihuahua, Mexico - Álvarez-Izazaga, Marsela Alejandra; Galindo-Gómez, Carlos; Roldán-Amaro, José Antonio; Saucedo-Arteaga, Gabriel; Díaz-Martínez, Margarita; Chávez-Villasana, Adolfo; Cuchillo-Hilario, Mario (Anales de Psicología / Annals of Psychology, 2022)
This study aimed to compare the general and health care characteristics of young children of migrant and non-migrant mothers from indigenous Tarahumara communities in Chihuahua, Mexico, and to evaluate the association between child risk for neurodevelopment delay with parental practices of early childhood stimulation. Male and female children aged 12 to 48 months were studied in two groups: 1) children of migrant mothers residing in urban settlements and 2) children of non-migrant mothers residing in their native rural localities. Prevalence of the risk of moderate to severe neurodevelopment delay (MSND) was greater in children of migrant mothers as compared to non-migrant mothers (75.6%, CI95% [69.5, 80.8] vs. 59.8%, [51.4, 67.7], p = .003). The proportion of children who received adequate and favorable early stimulation (FTES) at home was greater in children of non-migrant mothers (p < .001). The migration of indigenous mothers to urban settlements was associated with child MSND (p = .03), as well as to insufficient early stimulation practices (p = .03). Consistent attendance at early childhood stimulation sessions through the Initial Education program was greater in children of non-migrant mothers (p = .01), and non-attendance predicted child MSND (p = .02).